LO066: H1-antihistamine administration is associated with a lower likelihood of progression to anaphylaxis among emergency department patients with allergic reactions. (2nd June 2016) - Kawano, T.; Grunau, B.E.; Gibo, K.; Scheuermeyer, F.X.; Stenstrom, R.
Abstract : Introduction: H1-antihistamines are often used to treat allergic reactions, however, the influence of H1-antihistamines on progression to anaphylaxis remains unclear. Among patients initially presenting with allergic reactions, we investigated whether H1-antihistamines were associated with a lower proportion of patients progressing to anaphylaxis during observation.Methods: This was a retrospective cohort study conducted at two urban EDs from 2007 to 2012. We included adult patients with allergy and excluded those who met criteria of anaphylaxis at first evaluation by medical professionals and/or received antihistamines before the evaluation. Primary outcomes of interest were the number of patients who developed anaphylaxis during observation at ED and/or transportation by EMS. Secondary outcomes were the number of biphasic reactions and severe anaphylaxis (defined as sBP<90; SpO2<92%; and/or confusion, collapse, loss of conscious, or incontinence). Logistic regression was performed comparing primary and secondary outcomes between H1-antihistamine treated and non-treated groups with propensity score adjustment of the baseline covariates. Number needed to treat (NNT) was calculated by adjusted absolute risk reduction of H1-antihistamine compared to non H1-antihistamine use on primary outcome.Results: This study included 1717 patients with allergic reactions, of whom 1228 were treated with H1-antihistamines. In the H1-antihistamine group 1.0% and 0.2% developed anaphylaxis and severe anaphylaxis, respectively; in the non-H1-antihistamine group 2.6% and 0.6% developed anaphylaxis and severe anaphylaxis, respectively. There were no biphasic reactions (0%, 95% confidence interval [CI] 0 to 0.17%). Administration of H1-antihistamines was associated with a lower incidence of subsequent anaphylaxis (adjusted odds ratio [OR] 0.23, 95% CI 0.10 to 0.53; NNT to benefit 49.1, 95% CI 41.6 to 83.3). There were no significant associations between H1-histamines administration and secondary outcomes.Conclusion: Among ED patient with allergic reactions, H1-antihistamine administration was associated with a lower likelihood of progression to anaphylaxis. These findings suggest that H1-antihistamines should be administered early in the care of patients with allergic reactions.